The Effect of High Temperature on α-Amylase Enzyme Activity in the Germination of Several Rice Varieties (Oryza sativa L.) - Afrima Sari (Department of Crop Science, Faculty of Agriculture, Andalas University, 2021)
High temperatures can affect plant morphophysiological changes and enzyme denaturation that can interfere with the germination process. This research aims to study the effect of temperature changes on the α-amylase enzyme activity of several rice varieties germination. The research applies Factorial Experiment in Completely Random Design, where the first factor is four levels of rice varieties, Anak Daro, Batang Piaman, Cisokan, and Inpari 30. The second factor is temperature level, 28 0C, 32 0C, 36 0C, 40 0C, 44 0C and 48 0C. Results showed that the activity of the α -amylase enzymes of the four varieties increased when the temperature increased to reach the optimal temperature, and denaturation began to occur above that temperature. The highest enzyme activity of α-amylase of Anak Daro, Cisokan and Inpari 30 varieties at 48 0C is 0,14 micromol, 0,365 micromol dan 0,191 micromol. In contrast the optimum enzyme activity of α-amylase of Batang Piaman variety at a temperature of 40 0C is 0,237 micromol and when the temperature rises to 48 0C a decrease in the activity of the α-amylation enzyme is 0,138 micromol. The variation in the activity of α-amylase enzymes in the four varieties is probably due to genetic differences and sucrose content. The Batang Piaman and Cisokan varieties can only germinate up to 36 0C, while the Daro and Inpari 30 varieties can germinate up to 40 0C.